Theory of oscillations performed by tools in spiral potato separator - Bulgakov, Volodymyr; Holovach, I.; Ruzhylo, Z.; Fedosiy, I.; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; J. Olt, J. (My University, 2020)
The aim of this study is to provide for the intensification of the process of removing impurities from the potato heap by oscillating devices, which takes place, when potato tubers are cleaned in the spiral separator during their lifting. The authors have devised a new design of the spiral separator, which can be used in the process of lifting potatoes from the soil. It comprises cantilever cleaning spiral springs, which in their simultaneously rotary and oscillatory motion clean and transport the potato tubers with good quality. However, the removal of impurities from the cleaning area and the cleaning of the side surfaces of potato tuber bodies from the stuck soil can be significantly more effective, if the spiral springs perform their oscillatory motions in the longitudinal and vertical plane during their operation more intensively. In order to achieve that, the authors have worked out a new theory of the oscillatory motion of the cleaning spiral working under the action of the potato heap. That promotes the intensification of the process of cleaning potato bodies from the stuck soil. The authors have generated a new partial differential equation, which describes the oscillations of the cantilever cleaning spiral. The PC-assisted numerical solving of the said differential equation and further numerical modelling have made it possible to obtain the analytic expressions of the relations between the change in the helix pitch distance of the cleaning spiral and its deformation, in particular, the simultaneous longitudinal extension and transverse bending. That result, in its turn, provided for finding the maximum limit amount of the above-mentioned deformation under the condition that the potato tubers may not fall through the spaces between the spiral turns, taking into account the design and kinematic parameters of the cleaning spiral itself, the material it is made of and the process-dependent mode of operation of the separator. As a result of the PC-assisted numerical modelling, it has been found that the total deflection of the spiral on its length varies within the range of 0 to 0.05 m under the following parameters: angular velocity of rotation of the spiral ω = 30 rad s-1, density of the material of the spiral ρ = 7,700 kg m-3, elastic modulus Е = 2∙1011 Pa, cleaning spiral bar stock radius r = 8.5 mm and a uniform load intensity of 1,000 N m-1. Such variation ensures the good quality of cleaning and transportation of potato tubers. According to the results of the PC-assisted numerical calculations, the helix pitch distance of a cleaning spiral with the above parameters and the original helix pitch distance S = 48 mm, due to the spiral’s deformation under the proposed transverse oscillations, can change up to 54 mm, which makes impossible for potato tubers to fall out of the cleaning unit. Experimental studies fully support the results from the theoretical calculations to determine the displacement of the ends of the cleaning unit’s spiral springs.
Keywords: cleaning unit; deformation; oscillatory motion; potato; soil